High prevalence of hypertension and myocardial infarctions in Saudi adult female population with blood type A - Farshori, Mohammad Parvaiz; Ghareeb Alrashdan, Yasir; AlTamimi, Raiya Khaled Ali; Houmood Alshammari, Hayam Abdullah; Alshammari, Mohammed Saqer; Saleh Alageel, Abrar Hamad; Naafa, Maha Al (International Journal Of Community Medicine And Public Health, 2018)
Background: There is high prevalence of obesity and smoking in Saudi population. Both are major risk factors for developing hypertension (HT) and myocardial infarctions (MI). Associations between hypertension, MI and ABO blood groups have been shown but they are inconsistent. To date no such studies have been done in Saudi Arabia to determine association between ABO blood groups and prevalence of smoking, hypertension and MI in Saudi female patients. Methods: 432 control females were randomly selected and distribution of ABO and Rh antigens was statistically analyzed and compared with 78 smokers, 219 hypertensive and 311 MI female patients admitted to King Khalid hospital between the periods of August 2017 to May 2018. Results: Among controls 3.2% were smokers, 7.6% hypertensive and 13.2% diabetics. Among hypertensive 7.8% were smokers and 46.6% were diabetics. Likewise we also found statistically significant increase in prevalence of smoking (9.9%) and diabetes (48.2%) in MI female patients. Additionally about half of MI patients (49.8%) were hypertensive. 85.9% controls were Rh+ and 14.1% were Rh-. Rh+ subjects were significantly higher in hypertensive and MI patients also. O+ was most prevalent and AB+ was least prevalent in all groups. Conclusions: Statistically there was no difference between distributions of, B-, B+, AB-, AB+ blood groups, however there was high prevalence of A blood group in hypertensive (31.4%) and female MI patients (31.2%) as compared to A blood group among controls (24.8%). Distribution of O blood group wassignificantly lower in hypertensive (42%) and MI patients (41.5%) as compared to controls (53.1%).